SURVEI STATUS GIZI MURID SD NEGERI NO. 117 SAOHIRING SINJAI TENGAH - Awal, Asri; ilyas, muslim bin; syamsuddin, muh syachrul (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2024)
This research is descriptive (independent variable). Thepopulation was 32 grade 4 elementary school students and thefemale sample was selected using non-random sampling usingpurposive sampling technique. In this case, gender, age, heightand weight were taken into consideration. A sample of 15female students in class 4 was taken into consideration. Thedata analysis technique used was descriptive percentages.Based on the results of data analysis in this study, it can beconcluded as follows: the nutritional status of fourth gradefemale students at SD Negeri No. 117 Saohiring Sinjai Tengahvaries based on nutritional level, including: low (less) 13people = 86.66%, ideal 2 people = 13.33% . And obtainedmean value = 14.9127 with standard deviation = 2.54423,variance = 6.473, range = 8.67= minimum = 12.21, andmaximum 20.88. So it can be concluded that the nutritionalstatus of class IV female students at SD Negeri No. 117Saohiring Sinjai Tengah is predominantly in the low (poor)category